2016
DOI: 10.1111/dote.12457
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of peroral endoscopic myotomy for achalasia after failed endoscopic interventions

Abstract: With advances in natural orifice transluminal endoscopic surgery, peroral endoscopic myotomy (POEM) has become a novel treatment for esophageal achalasia. In this study, we investigated the feasibility and safety of POEM in patients with achalasia after failed endoscopic interventions. Data on all patients undergoing POEM treatment of achalasia were collected prospectively. We enrolled 61 patients who underwent POEM for achalasia between July 2011 and January 2014. The preoperative intervention group included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…The other systematic reviews showed that POEM is more effective than HM in terms of relieving dysphagia with short‐time follow‐up, though POEM is associated with a much higher incidence of postoperative gastroesophageal reflux disease (GERD) 15,16. Recently, some studies have shown that POEM was effective even in patients who previously failed endoscopic procedures or HM 17-31. However, the number of patients who had POEM after failed conventional endoscopic treatment or HM was limited in each study and the therapeutic yield of POEM as salvage therapy has not been well evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The other systematic reviews showed that POEM is more effective than HM in terms of relieving dysphagia with short‐time follow‐up, though POEM is associated with a much higher incidence of postoperative gastroesophageal reflux disease (GERD) 15,16. Recently, some studies have shown that POEM was effective even in patients who previously failed endoscopic procedures or HM 17-31. However, the number of patients who had POEM after failed conventional endoscopic treatment or HM was limited in each study and the therapeutic yield of POEM as salvage therapy has not been well evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…[113][114] POEM is a treatment option in cases for which PBD failed, as well as an initial treatment for achalasia (Table 7). 77,109,[115][116][117][118][119][120][121][122] Large-scale observational studies including patients in whom PBD failed have reported that POEM is a safe and effective treatment option. 96,117,120 Prior treatment did not increase the risk of POEM-related adverse events.…”
Section: Management Of Achalasia Recurrence After Initial Treatmentmentioning
confidence: 99%
“…Unfortunately, most of the major adverse events were related to unrecognized intraoperative mucosal perforation. Some recent studies (7,37,38) found no difference in adverse events or efficacy after treatment with POEM vs Heller in patients treated with different previous therapies (dilation, Botox, and surgery) (4,7,21,(38)(39)(40)(41) . However, a separate prior study by Ren et al (42) showed a higher complication rate in POEM, perhaps related to the learning curve.…”
Section: Discussionmentioning
confidence: 98%